Preference for Novelty and Price Behaviour - Silvia Bertarelli; Roberto Censolo (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
In this paper we motivate a specific formulation for preference that exhibits both love for variety and love for novelty. This enables to investigate the effects of ageing of imperfect substitutes, as they became progressively old-fashioned, due to the obsolescence of their aesthetic features. First, we assume that the industry is divided into several sub-markets, each dominated by a single firm that produces a variety of a given vintage. We show that equilibrium prices decrease, as goods become older. Assuming a fixed cost to be paid, the evolution of demand determines the equilibrium number of varieties at the point where the oldest vintage firm earns zero profits. Second, we consider the model under a free entry condition assumption. Each sub-market of a given vintage is saturated with a number of varieties such that the market share of each firm is barely sufficient to realise zero profits. We show in a particular case that, in equilibrium, markets of the youngest varieties are characterised by a larger number of firms than markets offering older varieties. More specifically, the lifetime horizon of each variety will be characterised by decreasing prices accompanied by increasing demand levels.
Keywords: 330